2019
DOI: 10.1021/acsaelm.9b00030
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Mechanisms of Local Interfacial Resistive Switching in LaMnO3+δ

Abstract: Manganite perovskites exhibit promising resistive switching properties, for which the understanding of the related microscopic physicochemical changes taking place is still rather scarce. In this work the resistance of a LaMnO3+δ thin film has been locally tuned within a range of 2 orders of magnitude using conductive atomic force microscopy. With the use of X-ray photoemission electron microscopy it has been possible to simultaneously unravel composition and work function modification related to changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 58 publications
3
18
0
Order By: Relevance
“…It is observed in the initial LRS branch and at low voltage in HRS (| V appl | < 1 V). The presence of a nonohmic behavior after RESET indicates a modification of the transport mechanism due to the switching process, as discussed in our previous works. , …”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…It is observed in the initial LRS branch and at low voltage in HRS (| V appl | < 1 V). The presence of a nonohmic behavior after RESET indicates a modification of the transport mechanism due to the switching process, as discussed in our previous works. , …”
Section: Resultssupporting
confidence: 61%
“…The La 3d photoelectron peak of lanthanum compounds shows very prominent satellite features due to core–hole screening processes triggered by charge transfer between the unoccupied 4f valence orbitals and 2p orbitals of oxygen. , Thus, in the resulting La 3d 5/2 spectrum, a main peak (cf 0 ) and two satellite peaks (cf 1 L) show up, where c and L denote a core-hole in the La 3d 5/2 states and a ligand O 2p hole, respectively . In our previous study, we demonstrated the direct relationship between the oxygen content in the La surrounding and the ratio of the satellite and main peak areas …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The reasons for fast oxygen diffusion along extended defects in LSMO are not clear, [21][22][23] however; such knowledge is essential for tuning oxide-ion transport in LSMO for application as a cathode material in solid oxide fuel cells (SOFC) [24][25][26][27] or as the active material in memristive devices. [28][29][30][31][32][33][34] In ionic solids, there are two possibilities to explain the pheno menon of fast diffusion along dislocations [23] (see Figure 1a): (i) diffusion along the dislocation core is faster than in the bulk on account of the activation barrier for ion migration being lower in the core than in the bulk, as is the case in metals; (ii) the concentration of the defects responsible for diffusion is strongly enhanced in a space-charge tube surrounding the dislocation. [23,35,36] For LSMO, literature provides at present an unclear picture.…”
mentioning
confidence: 99%
“…[10][11][12][13] Therefore, the valence state of the material is strongly correlated to the oxygen content and Mn4+ can be seen as a dopant. [14] We recently investigated the microscopic mechanisms of local interfacial RS in LaMnO3+ by conductive atomic force microscopy (c-AFM) [15] and highlighted that the change in resistance is associated with a drift of oxygen ions to the surface and the concomitant variation in the Mn valence state, which results in modifications in the transport mechanism. However, the configuration used presents several specificities (e.g.…”
mentioning
confidence: 99%